2019
DOI: 10.1128/jvi.00157-19
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus 5 E1A Interacts with E4orf3 To Regulate Viral Chromatin Organization

Abstract: Human adenovirus expresses several early proteins that control various aspects of the viral replication program, including an orchestrated expression of viral genes. Two of the earliest viral transcriptional units activated after viral genome entry into the host cell nucleus are the E1 and E4 units, which each express a variety of proteins. Chief among these are the E1A proteins that function to reprogram the host cell and activate transcription of all other viral genes. The E4 gene encodes multiple proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Low passage (<20) A549 cells with endogenous expression of the 13S encoded E1A isoform of HAdV-5 (A549-13S), the 12S encoded isoform of HAdV-5 E1A (A549-12S) or empty vector transduced control cells (A549-EV) were cultured in Dulbecco’s modified Eagle’s medium (DMEM) with 4.5 g/L glucose, L-glutamine, sodium pyruvate, and phenol red (Wisent Inc, Saint-Jean-Baptiste, QC, Canada) supplemented with 10% fetal bovine serum (Wisent Inc), and 1% penicillin-streptomycin (Wisent Inc). The A549-13S cells were previously described in Soriano et al [ 23 ] as A549-E1A289R cells. These cells and the A549-12S and A549-EV cells were generated concurrently as the A549-13S cells and in a similar manner.…”
Section: Methodsmentioning
confidence: 99%
“…Low passage (<20) A549 cells with endogenous expression of the 13S encoded E1A isoform of HAdV-5 (A549-13S), the 12S encoded isoform of HAdV-5 E1A (A549-12S) or empty vector transduced control cells (A549-EV) were cultured in Dulbecco’s modified Eagle’s medium (DMEM) with 4.5 g/L glucose, L-glutamine, sodium pyruvate, and phenol red (Wisent Inc, Saint-Jean-Baptiste, QC, Canada) supplemented with 10% fetal bovine serum (Wisent Inc), and 1% penicillin-streptomycin (Wisent Inc). The A549-13S cells were previously described in Soriano et al [ 23 ] as A549-E1A289R cells. These cells and the A549-12S and A549-EV cells were generated concurrently as the A549-13S cells and in a similar manner.…”
Section: Methodsmentioning
confidence: 99%
“…Since E1A is known to interact with and modulate the activity of many host factors (see a comprehensive review by [83]), it is possible that the deletion of E1A residues 11-13 impacts more than its interaction with E4orf3. On viral genomes, transcription is reduced, histone occupancy increases, and E1A occupancy decreases only when E4orf3 is expressed in the presence of E1A compared to a control vector [143]. Based on these observations, E4orf3 seems to facilitate the association of host histone proteins with viral genomes and therefore modulate transcription.…”
Section: Impact Of E4orf3 On Host Chromatin and Chromatinization Of Vmentioning
confidence: 93%
“…A recent study suggests that E4orf3 may have a similarly repressive effect on transcription from viral genomes that is mediated through a heretofore unreported interaction between E4orf3 and E1A [143]. E1A co-immunoprecipitates with E4orf3 from cells that ectopically express an epitope-tagged copy of E4orf3 and are infected with E3D Ad5 demonstrating that E1A and E4orf3 interact during infection.…”
Section: Impact Of E4orf3 On Host Chromatin and Chromatinization Of Vmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that shortly after reaching the nucleus, HAdV DNA associates with histones and assembles into a chromatin-like structure similar to that of the host genome ( Giberson et al, 2012 , 2018 bib_Giberson_et_al_2012 bib_Giberson_et_al_2018 ; Komatsu and Nagata, 2012 ; Lynch et al, 2019 ; Ross et al, 2011 ; Wong et al, 2013 ). Virus-encoded genes are expressed from this template, and expression can be regulated by cellular epigenetic modifiers ( Hsu et al, 2018 ; Komatsu et al, 2011 ; Soriano et al, 2019 ). Although only a subset of cellular proteins involved in regulating the HAdV genome have been identified to date, these observations raise the possibility of targeting such proteins in order to inhibit viral gene expression and replication.…”
Section: Introductionmentioning
confidence: 99%